Evaluation of prognostic factors in Egyptian patients suffering from Bell’s palsy - Osama Yacoub; Mona Hussein; Rehab Magdy; Mohamed Ahmed Mohamed; Hanaa Ali Hafez; Doaa Mekkawy (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Bell’s palsy is common neurological disease. It is treated mainly by steroids with different physiotherapy (PT) modalities such as electrical stimulation, massage, exercise, and infrared. Low-level laser therapy (LLLT) also showed promising results. In this study, we aimed to investigate relevant factors related to the patients, disease, and treatment to explore their prognostic values in Egyptian patients. Results The age ranged from 24 to 50, with a median of 39. Two (1.4%) patients were pregnant. Hypertension (HTN) was the most common comorbidity found in 49.3%, followed by diabetes mellitus (DM) then ischemic heart disease (IHD). Around 98.6% of cases had unilateral palsy. The majority (81.2%) of cases were treated with steroids, and around 50% of cases received added-on laser physiotherapy. Around two-thirds (65.9%) of cases had a favorable outcome. Old age, DM, hepatic disorder, and pregnancy were associated with poor recovery, while steroids and laser therapy were associated with good outcomes. The regression model revealed that treatment with steroids and laser therapy increased the odds of favorable outcome by 4.317 (CI: 1.533–12.157) and 2.238 (CI: 1.019–4.915) times, respectively. Conclusions Old age, comorbid diseases, and pregnancy worsen the prognosis. However, steroid and laser physiotherapy improve outcomes and better recovery.